A lumen sizing workhorse guidewire for peripheral vasculature: Two functions in one device. Issue 1 (15th May 2013) - Svendsen, Mark C.; Choy, Jenny S.; Ebner, Adrian; Bigelow, Brian; Sinha, Anjan; Moussa, Issam; Akingba, A. George; Combs, Bill; Kassab, Ghassan S.
<x xml:space="preserve">Abstract</x> Objectives Ideally, guidewires used during peripheral vasculature (PV) interventions could serve both as a therapy delivery platform and a diagnostic tool for real‐time vessel sizing (2‐in‐1 function). Background Vascular imaging modalities, like intravascular ultrasound (IVUS), used during lower PV interventions, can improve outcomes versus angiographic assessment alone, but are rarely used due to added time, cost, and required clinical training/interpretation. Methods A 0.035″ bodied 0.035″ conductance guidewire (CGW) is described here as a vascular navigation and diagnostic real‐time PV sizing tool. When attached to a console, the CGW creates a safe, electric field to determine vascular size through simultaneous voltage measurements. Results The CGW showed functionality as a workhorse guidewire on the bench (torqueability and trackability equivalent to a Wholey guidewire) and in vivo (over‐the‐wire stent deployment in domestic swine and first‐in‐man study with no major adverse events). Validation of CGW sizing versus the true diameter and IVUS was completed in 4–10 mm diameter phantoms on the bench and in swine and showed virtually no bias with excellent repeatability and accuracy (i.e., CGW repeatability: swine phantom bias = 0.03 ± 0.09 mm (1.3% error). CGW vs. true diameter: in vivo bias = 0.14 ± 0.15 mm (2.7% error). IVUS vs. true diameter: swine phantom bias = 0.01 ± 0.36 mm (4.7% error). CCW vs. IVUS: swine phantom bias = 0.13 ± 0.26mm (3.8% error)). Conclusions Real‐time, accurate, and safe PV dimension assessment and therapy‐delivery (2‐in‐1 function) is possible using a novel workhorse 0.035″ bodied CGW. © 2013 Wiley Periodicals, Inc.